1979
DOI: 10.1177/014860717900300606
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition Utilization: Evaluation of an Educational Protocol and Consult Service

Abstract: A two part study was undertaken to evaluate the effectiveness of an educational protocol and consult service on parenteral nutrition (PN) utilization. Forty-one patient admissions were evaluated retrospectively and nine prospectively. Average length of hospital stay and number of days on PN were decreased significantly (p less than .05). Frequency of adverse effects were also decreased significantly (p less than .05). A positive trend toward selection of patients for enteral rather than PN was evidenced. Utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 6 publications
1
42
0
Order By: Relevance
“…Using the criteria for classification of studies promulgated by the National Health and Medical Research Council, no randomised‐controlled trails were identified. All 11 studies were comparative in design, 1,2,4,5,7,12–17 four with concurrent controls 2,4,5,12 and seven with historical controls 1,7,13–17 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the criteria for classification of studies promulgated by the National Health and Medical Research Council, no randomised‐controlled trails were identified. All 11 studies were comparative in design, 1,2,4,5,7,12–17 four with concurrent controls 2,4,5,12 and seven with historical controls 1,7,13–17 …”
Section: Discussionmentioning
confidence: 99%
“…The remaining study was conducted in two hospitals, one hospital was used as the intervention and the other as the control group 5 . The included studies were conducted in Spain, 13 the USA, 1,2,4,7,12,15–17 Singapore 14 and the UK 5 . The study period ranged from 2 weeks 2 to 3 years 17 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations